Gait parameters, functional mobility and fall risk in individuals with early to moderate primary open angle glaucoma: a cross-sectional study - Gomes, Henrique de Alencar (Braz J Phys Ther, 2018)
OBJECTIVE: This study investigated the influence of early to moderate primary open angle glaucoma on gait, functional mobility and fall risk. METHODS: Thirty-three participants in the early and moderate stages of primary open angle glaucoma and 34 asymptomatic controls participated in the study. Spatiotemporal gait data were obtained with the GAITRite system and included: velocity, cadence, step length, base of support, swing, stance and double support times. Functional measures included the Timed Up and Go test, the Five-Repetition Sit-To-Stand test and the Dynamic Gait Index. Fall risk was measured using the Physiological Profile Assessment. RESULTS: The variables contrast sensitivity, proprioception and the Timed Up and Go and Dynamic Gait Index tests were significantly different between groups. In addition, the glaucoma group presented significantly higher risk of falling compared to the control group. Individuals in the early and moderate stages of primary open glaucoma presented mobility and sensory deficits that increase the risk of falling. CONCLUSIONS: The results of this study suggest that adding the Timed Up and Go and Dynamic Gait Index tests to routine physical therapy assessment of individuals with early glaucoma could be useful. Rehabilitation programs should focus on maintaining and/or improving mobility and balance, and prevention of falls in this population.